Vertebrate taphonomy of the Ischigualasto Formation - Colombi, Carina Ester (2012)
Trends of preservation are established on the basis of 385 fossil occurrences in the Ischigualasto Formation. The distribution and preservational quality of vertebrate fossils are related to sedimentary facies and stratigraphic position and follow trends in basin evolution and paleoclimate. Fossils in the Ischigualasto Formation are mainly concentrated along the margins of the basin. Floodplain deposits preserve ca. 88% of fossils, which range from unidentifiable fragments to articulated skeletons. The remaining fossil occurrences (ca. 12%) come from coarser-grained fluvial channel deposits and exhibit variable preservational quality, including some well-preserved cynodont skulls. Fossils in the basal La Pe˜na Member (ca. 4% of occurrences) are generally highly weathered and disarticulated with hematitic permineralization. The majority of collected specimens (ca. 65% of occurrences) come from the overlying Cancha de Bochas Member and range from isolated bones to articulated skeletons. Calcite, rather than hematite, is the predominant agent of permineralization. The succeeding Valle de la Luna Member (ca. 30% of occurrences) preserves an association between vertebrate fossils and plant remains. Fossil preservation suggests prolonged exposure prior to burial under wetter conditions with superficial and penetrating precipitation of hematite. The uppermost Quebrada de la Sal Member of the Ischigualasto Formation is nearly barren of fossil remains.